Anthropogenic Aerosols Cause Recent Pronounced Weakening of Asian Summer Monsoon Relative to Last Four Centuries. Issue 10 (29th May 2019) - Liu, Yu; Cai, Wenju; Sun, Changfeng; Song, Huiming; Cobb, Kim M.; Li, Jianping; Leavitt, Steven W.; Wu, Lixin; Cai, Qiufang; Liu, Ruoshi; Ng, Benjamin; Cherubini, Paolo; et al.
Abstract: The Asian Summer Monsoon (ASM) affects ecosystems, biodiversity, and food security of billions of people. In recent decades, ASM strength (as represented by precipitation) has been decreasing, but instrumental measurements span only a short period of time. The initiation and the dynamics of the recent trend are unclear. Here for the first time, we use an ensemble of 10 tree ring‐width chronologies from the west‐central margin of ASM to reconstruct detail of ASM variability back to 1566 CE. The reconstruction captures weak/strong ASM events and also reflects major locust plagues. Notably, we found an unprecedented 80‐year trend of decreasing ASM strength within the context of the 448‐year reconstruction, which is contrary to what is expected from greenhouse warming. Our coupled climate model shows that increasing anthropogenic sulfate aerosol emissions over the Northern Hemisphere could be the dominant factor contributing to the ASM decrease. Plain Language Summary: Monsoonal rainfall has a certain influence on agriculture and industry in the regions of Asian Summer Monsoon (ASM). An understanding of the spatial‐temporal variability of the ASM and the associated dynamics is vital for terrestrial ecosystems, water resources, forests, and landscapes. We have developed a 448‐year ASM reconstruction back to 1566 CE using 10 tree ring chronologies from the margin region of ASM. We find that historical severe droughts and locust plague disasters during weak ASM events. The recent decreasing ASM trend persisting for over 80 years is unprecedented over the past 448 years. Coupled climate models show that increasing anthropogenic aerosol emissions are the dominant underlying factor. Our aim is that the time series will find a wide range of utility for understanding past climate variability and for predicting future climate change. Key Points: A 448‐year Asian Summer Monsoon reconstruction that extends back to 1566 CE was developed using an ensemble of 10 tree ring chronologies from northwest China The recent 80‐year decreasing trend of the Asian Summer Monsoon was unprecedented over the past 448 years Coupled climate models showed that the unprecedented decreasing trend was likely due to increasing anthropogenic aerosols